2005
DOI: 10.1113/jphysiol.2005.083188
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node dysfunction following targeted disruption of the murine cardiac sodium channel gene Scn5a

Abstract: We have examined sino-atrial node (SAN) function in hearts from adult mice with heterozygous targeted disruption of the Scn5a gene to clarify the role of Scn5a-encoded cardiac Na + channels in normal SAN function and the mechanism(s) by which reduced Na + channel function might cause sinus node dysfunction. Scn5a +/− mice showed depressed heart rates and occasional sino-atrial (SA) block. Their isolated peripheral SAN pacemaker cells showed a reduced Na + channel expression and slowed intrinsic pacemaker rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
113
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 43 publications
19
113
1
1
Order By: Relevance
“…Previous studies have demonstrated that Na v 1.5 is involved in action potential propagation, but both Na v 1.1 and Na v 1.5 contribute to the pacemaking in SAN (Haufe et al 2005). However, knockout of Na v 1.5 mice caused bradycardia, which elucidates the possibility of Na v 1.5 contribution to the pacemaking (Lei et al 2005). Thus, the true nature of the spontaneous rhythm generation, synchronization and propagation of cells remains an open question with Na + channel isoforms participation.…”
Section: Introductionmentioning
confidence: 54%
“…Previous studies have demonstrated that Na v 1.5 is involved in action potential propagation, but both Na v 1.1 and Na v 1.5 contribute to the pacemaking in SAN (Haufe et al 2005). However, knockout of Na v 1.5 mice caused bradycardia, which elucidates the possibility of Na v 1.5 contribution to the pacemaking (Lei et al 2005). Thus, the true nature of the spontaneous rhythm generation, synchronization and propagation of cells remains an open question with Na + channel isoforms participation.…”
Section: Introductionmentioning
confidence: 54%
“…Loss of function mutations in human cardiac sodium channels have been linked to atrial standstill (21), conduction system disease (22), sick sinus syndrome and bradyarrhythmia (19,20). Furthermore, a murine model with a partial loss of the pore-forming (alpha) subunits of the sodium channel essentially recapitulates the key features of sinus nodal dysfunction in humans (23).…”
Section: Discussionmentioning
confidence: 99%
“…An inward sodium current is also detectable in sinus node cells and is important for normal sinus node function (17,18). Furthermore, mice with a heterozygous mutation in Scn5a show sinus node dysfunction and age-dependent degeneration of sinus node tissue (19).…”
Section: Figurementioning
confidence: 99%